Metacognitive training in the acute psychiatric care setting: feasibility, acceptability, and safety - Fischer, Rabea; Nagel, Matthias; Schöttle, Daniel; Lüdecke, Daniel; Lassay, Franziska; Moritz, Steffen; Scheunemann, Jakob (Frontiers in Psychology, 2023)
Patients on acute psychiatric wards desire more psychosocial treatment than they receive, according to recent studies, but evidence-based interventions tailored to this setting are currently lacking. Metacognitive Training for psychosis (MCT) is a flexible, easy-to-administer group therapy that has been adapted to meet this demand (MCT-Acute). Thirty-seven patients with severe mental illness took part in MCT-Acute twice a week during their stay on a locked acute ward and were interviewed before, during, and after the intervention period regarding subjective utility, subjective adverse events, and symptom severity; attendance rates and reasons for absence were recorded. In addition, staff rated adverse events, symptom severity, and functioning (German Clinical Trial Register ID: DRKS00020551). Overall, most patients evaluated MCT-Acute positively and reported symptom stabilization. Staff also reported improvement in functioning. No clinician-rated adverse events related to participation in MCT-Acute were reported. Conducting MCT-Acute is feasible and safe and may contribute to meeting patients’, practitioners’, and researchers’ demands for more evidence-based psychotherapeutic interventions for the acute psychiatric care setting. Clinical Trial Registration ID: DRKS00020551, https://drks.de/search/de/trial/DRKS00020551